Species Diversity and The Importance of Charismatic Medicinal Plants in Ayer Hitam Utara Forest Reserve, Johor - Bt Nor Hassan, Nurul Hazirah; Bt Pa'ee, Furzani (Journal of Sustainable Natural Resources, 2023)
Medicinal plants in peat swamps have not received much attention in Malaysia in recent years due to land conversion in this peat swamp area. This study aimed to record the species diversity of medicinal plants in Ayer Hitam Utara Forest Reserve, to develop an interactive website containing medicinal plants in Ayer Hitam Utara Forest Reserve, and to collect feedback on user experience using the website by using an online survey. Data about species diversity was measured by Shannon-Wiener Index by doing random sampling with 10 m x 5 m quadrat. There are 21 species (14 families) of medicinal plants were identified. Clidemia hirta, Spondias dulcis and Vitex pinnata were among the highest number of individuals of each species that could be found. Fever, wound treatment, and stomachache, were the most common illness that uses these medicinal plants. Decoction method was the most typical way to prepare this herbal medicine. Koompassia excelsa is one of the new records of medicinal plants found in this Ayer Hitam Utara Forest Reserve which can lower cardiovascular risk, act as an antioxidant and help in wound healing. An interactive website was developed using StoryMap ArcGIS to document the collection. Based on feedback for the website, most of the respondents agreed that the website has good content and user-friendly. This documentation is crucial to preserve our natural resources for the future generation.